Formation of Technetium Salts in Hanford Low‐Activity Waste Glass. Issue 12 (22nd August 2016) - Soderquist, Chuck Z.; Buck, Edgar C.; McCloy, John S.; Schweiger, Mike J.; Kruger, Albert A.
Abstract : The distribution and physical form of technetium in a Hanford low‐activity waste (LAW) glass was examined with scanning electron microscopy (SEM) and X‐ray diffraction (XRD). A simulated Hanford LAW glass was spiked with varying amounts of potassium pertechnetate and melted at 1000°C. The glass was melted in a sealed quartz ampoule with the air pumped out, so that volatile material could leave the glass but would not be lost from the system. Previous studies have shown that technetium remains in the glass up to about 2000 ppm, but rises to the top of the melt as a separate salt phase above this concentration. Examination by SEM shows that crystals of technetium compounds appear to grow out of the hot glass, which implies that the hot glass was supersaturated in technetium salts. Some of the technetium compound crystals had apparently melted, but other crystals had obviously not melted and must have formed after the glass had partially cooled. The technetium compounds in the salt layer are KTcO4 and NaTcO4, according to SEM and XRD. No TcO2 was found in the salt phase, even though Tc(IV) has been previously reported in the glass.